Rural Investment Climate in Indonesia - McCulloch, Neil 1964- (Institute of Southeast Asian Studies, 2009)
It is a delight to see it published and available to a wide audience." - C. Peter Timmer, Visiting Professor, Program on Food Security and Environment, Stanford University; Non-Resident Fellow, Center for Global Development